Dampak Karakteristik Individu Dan Karakteristik Pekerjaan Terhadap Kinerja Karyawan : Studi Kasus PT. Bank Nagari Cabang Painan - Nynda Rahmatika; Zusmawati Zusmawati (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
Human resources are the key that must be paid attention to because human resources or workforce play an important role in the success and achievement of an organization's goals. The organization itself is a collection of several people who try to carry out the organization's goals as best as possible. By increasing the quality of human resources, it is hoped that it can improve employee performance. Every company will always try to improve the performance of its employees, with the hope that company and individual goals can be achieved. Work is a human obligation that must be fulfilled with the aim of meeting life's needs now and in the future. Working is not just about earning income and pursuing wealth, but working must also be based on the norms and rules that exist in the workplace.